Perancangan Pile Cap Menggunakan Metode Strut and Tie Model - Wijaya, Annisa; Sukarman (Jurnal Poli-Teknologi, 2024)
The design of the pile cap structure generally involves a conventional method that assumes that all areas are linear. The reality distribution strain in cross-section structure pile cap experiences non-linear strain. So it is necessary method close the analysis behavior pile cap actually, that is with the method Strut and Tie Model referring to SNI 2847:2019. Therefore, done study with the formulation problem How designing a reinforcement pile cap with three poles with the method Strut and Tie Model as a comparison configuration reinforcement and requirements material with method conventional. Research methods are done with stages studies literature, data collection, modeling form strut and tie, analysis calculation, up to detailed drawing of the reinforcement pile cap. Comparison configuration reinforcement flexible on method Strut and Tie Model follow the modeling lines element tie, whereas method was conventionally installed with spread reinforcement evenly throughout area pile cap. The strut and Tie Model Method consists of elements 1 (3D16), elements 2 and 3 (4D16) with a total length of reinforcement bending of 18884 mm. The method conventional consists of X direction (6D16) and Y direction (6D16) with a total length of reinforcement bending of 16530 mm. This matter proves that the strut and tie model produces more lots that need reinforcement amounting to 14.24%.   Keywords: Pile Cap, Three Piles, Strut and Tie Model, SNI 287-2019, Flexural Reinforcement